Human‐associated Staphylococcus aureus strains within great ape populations in Central Africa (Gabon). (11th February 2013) - Nagel, M.; Dischinger, J.; Türck, M.; Verrier, D.; Oedenkoven, M.; Ngoubangoye, B.; Le, G.; Drexler, J. F.; Bierbaum, G.; Gonzalez, J.‐P.; Lina, G.
Abstract The risk of serious infections caused by Staphylococcus aureus is well‐known. However, most studies regarding the distribution of (clinically relevant) S. aureus among humans and animals took place in the western hemisphere and only limited data are available from (Central) Africa. In this context, recent studies focused on S. aureus strains in humans and primates, but the question of whether humans and monkeys share related S. aureus strains or may interchange strains remained largely unsolved. In this study we aimed to evaluate the distribution and spread of human‐like S. aureus strains among great apes living in captivity. Therefore, a primate facility at the International Centre for Medical Research of Franceville (Gabon) was screened. We detected among the primates a common human S. aureus strain, belonging to the spa‐type t148. It was isolated from three different individuals of the western lowland gorilla (Gorilla gorilla gorilla), of which one individual showed a large necrotizing wound. This animal died, most probably of a staphylococcal sepsis. Additionally, we discovered the t148 type among chimpanzees (Pan troglodytes) that were settled in the immediate neighbourhood of the infected gorillas. A detailed analysis by pulsed field gel electrophoresis showed that the gorilla and chimpanzee isolates represented two closely related strains. To our knowledge, this is the first report of a human‐associated S. aureus strain causing disease in great apes. The simultaneous detection in gorillas and chimpanzees indicated an interspecies transmission of this S. aureus strain. Our results recommend that protection of wild animals must not only be based on habitat conservation, but also on the assessment of the risk of contact with human pathogens.